2022
DOI: 10.3389/fmed.2022.858115
|View full text |Cite
|
Sign up to set email alerts
|

A Height-Based Dosing Algorithm of Bupivacaine in Spinal Anesthesia for Decreasing Maternal Hypotension in Cesarean Section Without Prophylactic Fluid Preloading and Vasopressors: A Randomized-Controlled Non-Inferiority Trial

Abstract: BackgroundThere is a high incidence of maternal hypotension in spinal anesthesia for cesarean section. The aim of the study is to investigate whether there is a height-based dosing algorithm of bupivacaine that provides adequate anesthesia with less maternal hypotension.MethodsThere were 2 groups of 280 parturients who did not receive prophylactic fluid preloading: Test and Conventional group. In Test group, a height based dosing algorithm was used to confirm the dose of bupivacaine in parturients without prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…However, the height is associated with vertebral column length [ 7 ], which has an influence in the block level [ 8 ]. Thus, the local anesthetic’s dose should have an association with the height, which is confirmed by two studies [ 1 , 9 ]. In our last article, when using a constant bupivacaine dose, the shorter parturients have a higher occurrence rate of hypotension, a faster sensory block time or a higher proportion of complete motor block [ 1 ].…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…However, the height is associated with vertebral column length [ 7 ], which has an influence in the block level [ 8 ]. Thus, the local anesthetic’s dose should have an association with the height, which is confirmed by two studies [ 1 , 9 ]. In our last article, when using a constant bupivacaine dose, the shorter parturients have a higher occurrence rate of hypotension, a faster sensory block time or a higher proportion of complete motor block [ 1 ].…”
Section: Introductionmentioning
confidence: 58%
“…In previous study, we preliminarily verify that the bupivacaine dose depends on the parturient’s height in caesarean section under spinal anesthesia [ 1 ], but which needs to be further investigated. In addition, we have develop an algorithm of bupivacaine dose based on height in spinal anesthesia, which can provide sufficient anesthesia, but induce a low occurrence rate of hypotension in the parturients without prophylactic vasopressors and fluid preloading [ 1 ]. However, the anesthesia characteristic of this algorithm is not thoroughly clear, and it is unclear whether this algorithm is the optimal algorithm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, block level should be chosen based on height, as supported by two studies [85,86]. Huang et al showed that the block level was highly dependent on the height of the parturient when using a low dose of bupivacaine [83]. A lower dose of local anesthetic results in less blockade and reduces the incidence of hypotension at SA; however, it may cause incomplete analgesia and muscle relaxation [87].…”
Section: Non-pharmacological Measuresmentioning
confidence: 99%
“…Several studies have reported no statistical correlation between block level and height [80][81][82]. Huang et al [83] showed that the dose of local anesthetic was not adjusted according to height in many studies. This is an important point for the population of SEA, where most parturients are small.…”
Section: Non-pharmacological Measuresmentioning
confidence: 99%